IMPLEMENTASI PROGRAM IMUNISASI BCG DI PUSKESMAS SRONDOL KOTA SEMARANG - Natalia Scolastika Pandiangan; Aufarul Marom; Herbasuki Nurcahyanto (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2022)
Semarang City has BCG immunization target of 95%. The Srondol Health Center had the lowest BCG immunization achievement in Semarang City in 2021, which is 80.37%. This achievement is below the target set by the Semarang City Health Office. Ministry of Health Regulation No. 12 of 2017 concerning the Implementation of Immunization. This study aims to analyze the implementation of the BCG immunization program at the Srondol Health Center and to investigate the determining factors in its implementation. The research method used is descriptive qualitative and the data collection techniques using interviews, observations, and documentations. The implementation of the BCG immunization program at Srondol Health Center looks at the program implementation process and pays attention to the existence of committed resources which is BCG immunization facilities and infrastructure. The program implementation process includes funding, planning, vaccine distribution, logistics storage and maintenance, delivery or socialization of the BCG immunization program, and the implementation of immunization services. In the committed resources, researcher looks at the availability of infrastructure in the management of logistics and storage of vaccines as well as in the immunization activity. In the process of implementing the program, there were deficiencies in the socialization and implementation of immunization services. In committed resources, the availability of facilities and infrastructure is sufficient and in good condition. To investigate the determining factors of program implementation are using Edwards III theory with variables of communication, resources, disposition, and bureaucratic structure. Communication, disposition, and bureaucratic structure are the driving factors while resources is the inhibiting factor. The advice given is to hold socialization routinely in the working region of the health center and to add more officers to the position of coordinator of the immunization program.